Analisis Variabel dan Pola Hubungannya dalam Penelitian Pendidikan (Kajian Konseptual) - Diana Safitri; Jamaluddin Jamaluddin; M. Duskri (Journal of Innovative and Creativity, 2025)
Educational research demands clarity and accuracy in defining variables and understanding the patterns of relationships between them. This article aims to conceptually examine variables in-depth from their definitions and classifications to operational formulations and types of relationships in educational studies. This conceptual review uses literature from the last ten years through a library research approach. The results indicate that a solid understanding of variables significantly affects instrument validity, the choice of analytical methods, and research conclusions. The article also presents concrete examples of each variable type and relationship pattern, such as associative, comparative, and causal connections. Therefore, this study serves as a valuable conceptual reference for researchers, especially beginners, in designing structured, logical, and scientifically grounded educational research.